Phase transitions and dynamical properties of quasi-one-dimensional structures with hydrogen bonds - Stetsiv, R.Ya. (Condensed Matter Physics, 2012)
The frequency dependence of dynamical conductivity of the quasi-one-dimensional structures with hydrogen bonds is studies on the bases of pseudospin-electron model. It is taken into account the proton-electron interaction, external longitudinal field h, the tunneling hopping of protons, electron transfer and direct interaction between protons. The dependence of the electron concentration and mean number of protons on site on temperature and external field are obtained. The phase transition lines from uniform phase into charge ordered phase is determined. The dependence of the dynamical conductivity on temperature and field h and it changes at the phase transitions are obtained. На основi псевдоспiн-електронної моделi дослiджено частотну залежнiсть динамiчної провiдностi квазiо-дновимiрних систем з водневими зв’язками. В моделi враховано протон-електронну взаємодiю, зовнiшнє поздовжнє поле h, тунелювання протонiв, електронне перенесення i пряму протон-протонну взаємодiю. Отримано залежнiсть електронної концентрацiї i середньої заселеностi протонних позицiй вiд температури i поля h. Отримано лiнiю фазових переходiв з однорiдної фази до фази з модуляцiєю заряду. Дослiджено залежнiсть динамiчної провiдностi вiд поля h i температури та її змiни при фазових переходах.